Mirror Image Artifact Mimicking Heterotopic Pregnancy on Transvaginal Ultrasound: Case Series - Malhotra, Radhika (Department of Emergency Medicine, University of California, Irvine School of Medicine, 2014)
Vaginal bleeding in early pregnancy is a common emergency department complaint. Point-of-care ultrasound is a useful tool to evaluate for intrauterine ectopic pregnancy. Emergency physicians performing these studies need to be cognizant of artifacts produced by ultrasound technology, as they can lead to misdiagnosis. We present two cases where mirror-image artifacts initially led to a concern for heterotopic pregnancies but were excluded on further imaging.